LATEST TRENDS IN THE MARKET OF DAIRY PRODUCTS IN UKRAINE - Bochko , O.Yu.; Kuziak , V.V. (The actual problems of regional economy development, 2023)
The article reveals the latest trends in the dairy products market of Ukraine. The purpose of writing the article is the formation of the latest trends in the dairy market. Various general scientific and special research methods were used in the process of the work. In particular, inductive and deductive methods were used to analyze the dynamics of the cow population in Ukraine in all categories of farms. With the help of economic analysis and comparison, the analysis of the dynamics of the cow population in agricultural enterprises and enterprises of the population for 2011-2021 was carried out. And the forecast until 2025 was calculated. The graphic method was used to visualize the research results. The abstract-logical method was used for theoretical generalizations and the formation of conclusions. The dynamics of milk production in Ukraine are substantiated, and it is proved that it is determined by two main indicators - the number of livestock and the productivity of cows. During the last decade, a gradual decrease in the number of cows in Ukraine has been observed, which has become a stable negative trend. It was established that for 2011-2021 the number of cows decreased by almost 1/3: in 2011 its number was 2.63 million heads, and in 2021 - 1.67 million heads. The number of cows in agricultural enterprises (by 28%) and in households decreased. The tendency to decrease is also predicted until 2025. This is also indicated by the linear predictive model. In the structure of all farms, the largest specific weight is occupied by households, in most cases, they make up more than 75%. For 2020-2021, production volumes also decreased by 544.5 thousand tons. Over the years, the specific weight of all regions of Ukraine in the overall structure of the volume of milk production has decreased. It has been established that the increase in prices for dairy products can lead to a reduction in consumption, a shortage of milk, and an increase in exports. The influence of the seasonality factor on the price is substantiated. In addtion, dairy producers work under martial law, some even under fire. The number of imported dairy products is increasing in the Ukrainian market, and this poses a threat to Ukrainian producers. It should be noted that if the current conditions do not change, the trend of increasing imports will continue.